Evaluación andrológica en cerdos reproductores destinados a la producción de semen en la granja López Suarez Parroquia Guare - Alcivar Jurado, Odali Edith (2023)
Andrological evaluation is currently one of the most used means to evaluate whether the pig selected as a semen breeder does not have any morphology, whether its sperm concentration is of good quality and to be able to continue using the semen as artificial insemination. The objective of the work was to andrologically evaluate the breeding pigs destined for semen production at the López Suarez Parroquia Guare farm. Three breeding pigs of the German Pietrain, Pietrain Plus and Duroc breeds were used. Non-parametric statistics were used for the analysis of this research and the results will be presented in percentages, tables and graphs. The variables evaluated were volume, pH, mass motility, sperm concentration and sperm morphology. The macroscopic variable of semen, appearance and color were similar on days zero, four and seven. The Ph showed variation between days and breeds. Mass motility on days zero and four was very good, unlike on day seven it was good. In sperm morphology there were no numerical differences on day zero, while on days four and seven there were differences between the breeds under study. In the Analysis of the semen quality of the Pietrain Plus, German Pietrain and Duroc breeders, they presented numerical differences between days zero, four and seven as shown in tables four, five and six. The Pietrain plus and Duroc breeds obtained a greater ejaculate volume (300ml) and the German Pietrain breed had a lower ejaculate volume (250ml).